Economic policy, institutional development, and income growth: How Arab countries compare with other developing countries - Peter Nunnenkamp (Kiel Institute for World Economics (IfW), 2003)
Similar to most other developing countries, almost all Arab countries failed to catch up economically with advanced industrial countries. This paper discusses three possible explanations of the disappointing growth performance: (i) an insufficient reformmindedness of developing country governments, (ii) counterproductive policy recipes of the Washington Consensus and (iii) more deeply rooted barriers to growth related to institutional deficiencies prevailing in various developing countries. The empirical evidence for Arab countries and other developing countries provides little support to the first two hypotheses. By contrast, institutional development is shown to have a significant impact on policy-related variables and the growth performance of developing countries. For Arab countries as a group, institutional development is more advanced than for the control group of other developing countries. Yet, serious institutional deficiencies tend to constrain future growth in several Arab countries. These findings have important implications for national policymakers and the international community.
Keywords: O10; O57; 330; Washington Consensus; implementation deficits; effectiveness of reforms; institutional growth determinants; Wirtschaftswachstum; Wirtschaftspolitik; Anpassungsprogramm des IWF; Institutionalismus; Vergleich; Schätzung; Arabische Staaten; Entwicklungsländer